Narrativas de professores de flauta transversal e piano no ensino superior: a corporeidade presente (ou não) na aula de instrumento - Teixeira, Ziliane Lima de Oliveira (2016)
The research presented in this thesis is linked to the education and arts line of research at graduate program in education of the Federal University of Santa Maria. The research had as general objective to understand to what extent the concept of embodiment is present in teaching flute and piano narrated by teachers; and highlight specific objectives, one of the teachers narratives, those that refer to the attention with the health and welfare of the student; and analyze the narratives of teachers on their performance regarding the mind-body relationship in teaching flute and piano. I take ownership on embodiment concept from the theoretical perspective of Merleau- Ponty (2006), which bring to dialogue with researchers from the musician s health: Williamon and Thompson (2006); Brandfonbrener and Kjelland (2002); Wynn Parry (2004); Cowell and Hewitt (2011) among others. The research is presented starting from the vision of teaching music conservatorial (VASCONCELOS, 2002) and the teacher-student relationships (KINGSBURRY, 1988; LOURO, 2008; DEWEY, 2011). The methodology adopted is the Thematic Oral History (ROBERTS, 2002; MEIHY, 2005; PEREIRA DE QUEIROZ, 2008; MEIHY and HOLANDA, 2011), through narrative interviews (LOURO, 2004; JOVCHELOVITCH and BAUER, 2012) that were contextualized with the daily record (ALBERTI, 2005; FLICK, 2009) and data analysis was made from the Grounded Theory (CHARMAZ, 2009). Interviews were held with ten teachers of transverse flute and piano public universities in the South region of Brazil. Research approaches of research conducted by Louro (2004), Borba (2011) and Machado (2012) the methodology adopted for the same locus of research higher education of music and also by addressing issues of traditions and innovations in the teaching of music. As a result, we can highlight that respondents: (i) are anxious to look at the student as a unique individual, providing a personalized education, despite guidelines and repertories in common; (ii) seeking to be attentive to bad habits and physical wellbeing posture central to the good relationship with the instrument and the music, but not everyone knows how to guide the students, whereas there are limits on the formation of a music teacher; (iii) the concept of embodiment is present in some teaching practices, but others have a more traditional look, concerned only with good posture and health, being this thought directly related with the performance of the teachers in the mind-body relationship in teaching flute and piano. The embodiment of students and teachers is one of the main challenges encountered in the imbrication of traditions and innovations in narratives about flute and piano teaching for teachers of higher education. Although there is no unanimity on how to take this theme, there is consensus on the crucial importance of the subject among the teachers. It is expected that the findings of this thesis can benefit musicians, music students, instrument teachers, educators and researchers, in the areas of education, music education, music and musician's health.